Acrodermatitis enteropathica in the pediatric population: a literature review of real-world studies - Cui, Wanlin; Wang, Ningning; Shi, Mingyue; Xu, Xuegang; Jiang, Hongkun (Frontiers in Nutrition, 2025)
Acrodermatitis enteropathica (AE) primarily affects children and is characterized by periorificial and acral dermatitis, alopecia, and diarrhea. Currently, zinc remains an effective treatment for pediatric AE. However, there is a lack of consensus regarding the optimal dosage for zinc therapy. Furthermore, emerging evidence suggests that basic zinc supplementation may be ineffective in certain cases. Therefore, we performed a literature search using PubMed and Web of Science in July 2024, focusing on pediatric AE patients, and reviewed 190 articles involving 231 patients (aged < 18 years) to address the gaps in knowledge about hereditary and acquired zinc deficiencies in these patients and to evaluate cases occurring during metabolic disease decompensation. In summary, zinc deficiency was observed in 75.9% of the patients. Among the 174 AE patients who received zinc supplementation at various dosages, 159 (91.4%) demonstrated therapeutic efficacy, with 1–3 mg/kg/day as the most commonly used effective dosage. Additionally, zinc supplementation was frequently shown to be ineffective in patients with AE associated with metabolic disorders. It is imperative to address the underlying metabolic perturbations to achieve optimal management of this condition. Therefore, a comprehensive evaluation of pediatric patients is crucial when addressing cases of AE.